uspA gene-based phylogenetic analysis and antigenic epitope prediction for Escherichia coli strains of avian origin - Grakh, Kushal; Mittal, Dinesh; Prakash, Anand; Kumar, Ramesh; Jindal, Naresh (Frontiers in Veterinary Science, 2023)
Pathogenic Escherichia coli (E. coli) is responsible for various local and systemic infections in animal and human populations. Conventional methods for the detection and identification of E. coli are time-consuming and less reliable for atypical strains. The uspA gene has been widely used as a target for the detection of E. coli. The present study was aimed at phylogenetic analysis of the uspA gene sequences to determine the evolutionary relationships between the strains and other members of the Enterobacteriaceae family. In addition, the unique differences in the sequences of the current study with Salmonella and Shigella species were tested using Tajima's molecular clock test. Antigenic epitope prediction was performed to locate the B-cell epitope region of the UspA protein. Two E. coli isolates of avian origin and strains from the National Center for Biotechnology Information (NCBI) database were used for prediction. The Immune Epitope Database (IEDB) server, Bepitope, ABCpred, SVMTrip, and ElliPro server were used to identify B-cell epitopes. The 3-D structure was predicted using SWISS-MODEL. Phylogenetic analysis of the isolates from the current study revealed that both OM837340 and OM837341 sequences from the current study had maximum nucleotide homology (nt) of 99.87-100% with E. coli isolates and minimum nt homology of 84.08% with Salmonella Enteritidis and S. Hissar. The isolates in the current study had a homology of 98.87%, while the homology with Shigella species was 99.25%. Seven silent mutations were observed in the coding region of the UspA protein of ECO9LTBW (current study). Modeling of the UspA protein revealed a maximum homology of 67.86% with the Protein Data Bank in Europe (PDBe), also validated by the Ramachandran plot. No significant differences were found in the coding regions of uspA of Salmonella, Shigella, and E. coli with Tajima’s test. For the E. coli isolates, a total of 24 linear B-cell and seven discontinuous epitopes were predicted using in-silico analysis. When the results of the predicted peptides were compared, two peptides, namely ARPYNA and YSDLYTGLIDVNLGDMQKRISEE, were found suitable candidates. In conclusion, the uspA gene appears to be conserved among E. coli isolates and can be used for molecular detection.